Bone properties in child and adolescent male hockey and soccer players - Falk, B.; Braid, S.; Moore, M.; Yao, M.; Sullivan, P.; Klentrou, N. (Journal of Science and Medicine in Sport, 2010)
Children and adolescents who train extensively in high-impact, weight-bearing activities have enhanced bone mineral density. The purpose of this study was to evaluate bone strength, as reflected by quantitative ultrasound (QUS, Sunlight Omniscence), of child (10-12 yrs old) and adolescent (14-16 yrs old) male soccer and hockey players in comparison with age-matched controls. The groups included 30 child (CH) and 31 adolescent (AH) hockey players, 26 child (CS) and 30 adolescent (AS) soccer players, as well as 34 child (CC) and 31 adolescent (AC) healthy, non-athletic, age-matched controls. All athletes trained at an elite level year-round, with no difference in training volume between groups. Ultrasound speed of sound (SOS) was measured at the distal-radius and mid-tibia. In both age groups, hockey players were the heaviest and had the highest fat-free mass. No differences were found among groups in total energy intake, calcium or vitamin D intake. Radial and tibial SOS increased with age. Hockey players had higher radial SOS in both age groups (children: CH:3763 ± 74, CS:3736 ± 77, CC:3721 ± 88 m/s; adolescents: AH:3809 ± 105, AS:3767 ± 85, AC:3760 ± 94 m/s). Tibial SOS was higher in soccer players compared with controls. In spite of the higher body mass and fat-free mass in hockey players, their tibial SOS was similar to the non-athletes in both age groups. These findings support previous suggestions of sport-specific effects on bone strength. However, they need to be corroborated with longitudinal or prospective intervention studies.